2017
DOI: 10.1186/s12931-017-0524-y
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis of sputum cytokine-high profiles reveals diversity in T(h)2-high asthma patients

Abstract: BackgroundAsthma is characterized by a heterogeneous inflammatory profile and can be subdivided into T(h)2-high and T(h)2-low airway inflammation. Profiling of a broader panel of airway cytokines in large unselected patient cohorts is lacking.MethodsPatients (n = 205) were defined as being “cytokine-low/high” if sputum mRNA expression of a particular cytokine was outside the respective 10th/90th percentile range of the control group (n = 80). Unsupervised hierarchical clustering was used to determine clusters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 33 publications
2
51
0
6
Order By: Relevance
“…As indicated in the introduction, other recent studies in severe asthma have reported mainly transcriptomic gene expression data from various cell sources, including sputum, epithelial brush and biopsy, [24][25][26][27][28] in addition to more limited information for protein analysis. Proteins identified by Somascan in sputum supernatants of U-BIOPRED subjects presented only mild/moderate asthma, or severe asthma data (either smoking or not) compared to healthy controls subjects, without comparison between mild/moderate and severe asthma groups.…”
Section: Th2-ccl8/mcp2 Ccl13/mcp4mentioning
confidence: 99%
See 2 more Smart Citations
“…As indicated in the introduction, other recent studies in severe asthma have reported mainly transcriptomic gene expression data from various cell sources, including sputum, epithelial brush and biopsy, [24][25][26][27][28] in addition to more limited information for protein analysis. Proteins identified by Somascan in sputum supernatants of U-BIOPRED subjects presented only mild/moderate asthma, or severe asthma data (either smoking or not) compared to healthy controls subjects, without comparison between mild/moderate and severe asthma groups.…”
Section: Th2-ccl8/mcp2 Ccl13/mcp4mentioning
confidence: 99%
“…Moreover, this approach avoids reliance on measures of mRNA which lack linear association with actual protein synthesized . Although several recent reports have examined gene expression patterns in sputum and bronchial epithelial samples from subjects with severe asthma, these have included more limited information on corresponding protein analyses . One report from U‐BIOPRED, examining protein differences between 4 clinically identified cluster groups, found 9 differentially abundant sputum proteins in more severe clusters compared to moderate, well‐controlled asthma with normal FEV1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Both CRSwNP and asthma share common underlying pathophysiological mechanisms driving the disease (endotype), of which type 2 inflammation is the most prominent. 13,[17][18][19] Type 2 inflammation is characterized by the presence of eosinophilic airway inflammation associated with type 2-related cytokines (IL4, IL5, and/or IL13) and circulating and/or local IgE. 13,20 The management guideline in Europe for CRS, the European Position Paper on Rhinosinusitis and Nasal Polyps (EPOS), has been developed to provide physicians with comprehensive tables of levels of evidence and helpful management algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Both IL-25 and IL-33 cytokines have been related to airway changes which could be associated with the severity of asthma. Seys et al [18] analyzed the mRNA expression of sputum cells from patients with asthma characterized by poor asthma control and refractoriness; they found that IL-25, together with IL-5 and IL-17A, is associated with asthma endotypes refractory to CS. Cellular targets of IL-25 are not only basophils and other cells of innate immunity, e.g., type 2 innate lymphoid cells, mast cells, macrophages, and dendritic cells, but also structural cells like epithelial cells, endothelial cells, smooth-muscle cells, and fibroblasts [19].…”
Section: Discussionmentioning
confidence: 99%